Corrosion protection application of slippery liquid-infused porous surface based on aluminum foil - Tuo, Yanjing; Zhang, Haifeng; Chen, Weiping; Liu, Xiaowei (Applied surface science, 2017)
•Superhydrophobic surface and SLIPS are prepared on aluminum foil by a simple method.•The anti-corrosion capability of SLIPS is better than superhydrophobic surface in simulated seawater.•In acidic and alkaline environments, the anti-corrosion capability of superhydrophobic surface and SLIPS is completely opposite. Corrosion is a major problem for metal in marine systems. In this research, we fabricated a slippery liquid-infused porous surface (SLIPS) on the aluminum foil to protect the underneath metal. The as-fabricated samples were characterized with EDS, XRD, SEM, and contact angle meter. And the anti-corrosion property was evaluated by electrochemical measurements. The corrosion current density of SLIPS is ca.2 orders of magnitude lower than that of the untreated aluminum and superhydrophobic surface. And the impedance spectra of the SLIPS shows a large impedance semicircle with a diameter of several hundred kΩ.cm2. The SLIPS exhibits an outstanding corrosion protection capability, thus it has a broad application prospect in marine.